The Board Faultlines and Corporate Innovation Strategies Under the Influence of Property Rights Background and Institutional Environment - Zhang, Yan; Ma, Lianfu (Frontiers in Psychology, 2022)
This paper takes Chinese technology-intensive listed companies from 2009 to 2019 as the research sample to study the relationship between board faultlines and innovation strategy decisions of companies, and examine the impact of property rights background and institutional environment on the above relationship from the perspective of external governance environment of Chinese listed companies. The results show that social-related faultlines of the board of directors have negative influence on corporate innovation strategy decisions; cognitive-related faultlines have positive effect on corporate innovation strategy decisions. At the same time, this research proves that the property right background and institutional environment have a regulating role in the relationship between board faultlines and innovation strategy decisions, and can play an active role in the board faultlines.